Screening and Mapping for Head Blast Resistance in a Panel of CIMMYT and South Asian Bread Wheat Germplasm - He, Xinyao; Juliana, Philomin; Kabir, Muhammad R.; Roy, Krishna K.; Islam, Rabiul; Marza, Felix; Peterson, Gary; Singh, Gyanendra P.; Chawade, Aakash; Joshi, Arun K.; Singh, Ravi P.; Singh, Pawan K. (Frontiers in Genetics, 2021)
Wheat blast (WB) is a destructive disease in South America and its first outbreak in Bangladesh was in 2016, exposing great risk to food security of South Asian countries. A genome wide association study (GWAS) was conducted on a diverse panel of 184 wheat genotypes from South Asia and CIMMYT. Phenotyping was conducted in eight field experiments in Bolivia and Bangladesh and a greenhouse experiment in the USA. Genotypic data included 11,401 SNP markers of the Illumina Infinium 15K BeadChip and four additional STS markers on the 2NS/2AS translocation region. Accessions with stable WB resistance across experiments were identified, which were all 2NS carriers. Additionally, four 2AS accessions exhibited good WB resistance in the field but not in the greenhouse experiment, and a dozen moderately resistant 2AS lines that showed variation among experiments was identified. Significant marker-trait associations (MTA) were identified on chromosomes 1BS, 2AS, 6BS and 7BL; but only the ones on 2AS at the 2NS/2AS translocation region were consistently significant across experiments, and the rest three were significant only in two of the nine experiments. The resistant accessions identified in this study could be used in production in South Asian countries as a preemptive strategy to prevent WB outbreak.